Proceedings of the 7th International Conference on Tangible, Embedded and Embodied Interaction 2013
DOI: 10.1145/2460625.2460712
|View full text |Cite
|
Sign up to set email alerts
|

From wet lab bench to tangible virtual experiment

Abstract: SynFlo is an interactive installation that utilizes tangible interaction to make core concepts of synthetic biology accessible to the public. This playful installation allows users to create useful virtual life forms from standardized genetic components through the manipulation of augmented object that mirror scientific instruments in order to explore synthetic biology concepts and protocols. These virtual E. coli, can serve as environmental biosensors that when deployed into an environment represented by a ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…SixForty by Four-Eighty [7] is an art installation that uses a set of gestures for manipulating "tile" displays. SynFlo [59] is an interactive installation for introducing Synthetic Biology concepts to non-scientists. It utilizes Sifteo cubes to simulate a wet-lab bench and evoke gestures such as pouring and shaking.…”
Section: Active Token Interaction Languagesmentioning
confidence: 99%
“…SixForty by Four-Eighty [7] is an art installation that uses a set of gestures for manipulating "tile" displays. SynFlo [59] is an interactive installation for introducing Synthetic Biology concepts to non-scientists. It utilizes Sifteo cubes to simulate a wet-lab bench and evoke gestures such as pouring and shaking.…”
Section: Active Token Interaction Languagesmentioning
confidence: 99%
“…It does, however, allow users to apply various statistical tests on a dataset. Other examples include the G-nome Surfer [30], a multi-touch tabletop system for collaborative exploration of genomic databases; SynFlo [39], a tangible tabletop for introducing synthetic biology concepts to non-experts, and Eugenie [15], a tangible tabletop interface for helping synthetic biologists to explore of large datasets through the construction of complex queries. A more recent tabletop and active tangiblebased system called Sparse Tangibles [1] supports crossplatform collaborative gene network exploration using a Web interface.…”
Section: Related Workmentioning
confidence: 99%
“…Learning Collaboration Modeling Project GROPE [6] Visual and haptic displays Yes Unclear No Direct-manipulation animations [7] Interactive animations with auditory, visual, haptic feedback Yes No No VisANT [16] Conventional desktop interactions on a Web browser No No Partially Cytoscape [31] Conventional desktop interactions No No Partially Augmented Chemistry [13,14] Desktop and tangible interactions, and augmented reality Yes No Yes a-book [19] Augmented notebooks as active tangibles and stylus Yes Partially No Immersive interface for DNA [29] Various tangible 3D input devices No Unclear Unclear eLabBench [35] Stylus, mouse/keyboard, tangibles, and physical buttons Yes Yes Partially The G-nome Surfer [30] Multi-touch tabletop Yes Yes No Systems Dynamics [27] Tabletop and tangibles, and external display Unclear Yes Unclear SynFlo [39] Tabletop and active tangibles Yes Unclear No Eugenie [15] Tabletop and active tangibles Yes Yes No Sparse Tangibles [1] Tabletop and active tangibles Yes Yes No Kinesthetic Pathways [38] Tabletop [22]). It did not support model construction.…”
Section: Technique Interaction Modalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The evaluation of this prototype indicated that although we designed SynFlo to utilize gestures that mimic physical actions performed in the lab, users did not always understand these metaphors. This observation led to a redesign which resulted in a second prototype [34], which embedded the Sifteo Cubes within evocative concrete tangibles that represent lab instruments and afford physical actions such as shaking, pouring, and flipping. The toxin tokens and the interaction with the tabletop remained the same.…”
Section: Iterative Designmentioning
confidence: 99%